Application of Non-Destructive Techniques to the Recording and Modelling of Palaeolithic Rock Art - Gonzalez-Aguilera, Diego; Rodriguez-Gonzalvez, Pablo; Mancera-Taboada, Juan; Muñoz-Nieto, Angel; Herrero-Pascual, Jesus; Gomez-Lahoz, Javier; Picon-Cabrera, Inmaculada (IntechOpen, 2011)
None